Mechanical cell disruption of the green microalga Chloroidium saccharophilum: Effects on protein digestibility and aroma profile - Daniel Kurpan; Xin Gao; Rodrigo Cardeiras; Mariluz Bagnoud-Velásquez; Lucie K. Tintrop; Christian Rhême; Cédric Brügger; Ana Blanco Doval; Reto Portmann; Lotti Egger; Fabian Wahl; Alexandra Baumeyer Brahier (Journal of Applied Phycology, 2026)
The efficiency and outcomes of mechanically disrupting microalgal cell walls depend on various factors and are case-specific. In general, bead milling is reproducible and scalable, and it can successfully increase the digestibility of microalgal biomass. However, its effects on the aroma of microalgal biomass have not yet been assessed. This study is the first to report the use of the NanoWitt-100 bead mill to break down microalgal biomass. Optimization of processing time and cell concentration revealed that the optimal conditions were a milling time of 15 min, and a cell concentration of 50 g L −1 . Under these conditions, we then compared the in vitro protein and amino acid digestibility as well as volatile organic compound (VOC) profiles of undisrupted and disrupted samples. Bead milling substantially increased total protein digestibility from 62.2 ± 2.28 to 99.7 ± 0.06%. The digestibilities of all amino acids and the in vitro digestible indispensable amino acid scores (DIAAS) also increased. Although the release of VOCs increased in the disrupted biomass, the VOC profiles indicated an improvement in the final aroma of the biomass. This outcome was due to a reduction in acid concentration and an increase in ester concentration as a proportion of the total VOCs. Overall, these findings support further scalability tests, sensory analysis, and in vivo trials using microalgae disrupted with the bead mill NanoWitt-100.